Comparison of pressure gradient correlations for the spherical capsule train flow - Ulusarslan, D.; Teke, I. (TAYLOR & FRANCIS INC, 2008)
Design parameters (i.e., power of pumps, number of pumps, diameter of capsule, diameter of pipe, and geometry of pipe) of pipelines in which capsule flow can be developed if pressure drops (Delta P)(m) are caused by the two-phase flow are known. Therefore, designers are in need of a general model to calculate pressure drops. In the experimental part of this study, pressure drops that occur in the flow of low density (specific gravity of capsule: 0.87) spherical capsule (d = 0.08m) trains with water inside horizontal pipes (D = 0.1 m) were measured at 5-30% capsule transport concentrations, and the capsule flow mechanism was observed in Plexiglas pipes installed in the experimental equipment. A mathematical correlation developed to calculate the pressure drops of the flow of a low-density spherical capsule train is presented. Experimental results have been compared with general correlations regarding spherical capsule flows, and it is pointed out that available models are incompatible (average deviation exceeding 70-90%) with experimental results. However, comparison of the empirical correlation developed for pressure drops of spherical capsule train flow (2.5 x 10(4) < Re < 1.5 x 10(5)) with the experimental findings revealed an average deviation of 3.37% between the pressure drop values.
Keywords: hydraulic conveying; pipeline; pressure drop; spherical capsule; POLYMER ADDITION; VERTICAL TUBE; PIPELINE FLOW; DROPS; TRANSPORT; LIQUID; WATER; DRAG; Engineering